2021
DOI: 10.1101/2021.04.27.441510
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Aerosol Exposure of Cynomolgus Macaques to SARS-CoV-2 Results in More Severe Pathology than Existing Models

Abstract: The emergence of SARS-CoV-2 pandemic has highlighted the need for animal models that faithfully recapitulate the salient features of COVID-19 disease in humans; these models are necessary for the rapid down-selection, testing, and evaluation of medical countermeasures. Here we performed a direct comparison of two distinct routes of SARS-CoV-2 exposure, combined intratracheal/intranasal and small particle aerosol, in two nonhuman primate species: rhesus and cynomolgus macaques. While all four experimental group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 30 publications
7
14
0
Order By: Relevance
“…Disease signs were typically noted between Study Days 2-9. Clinical signs of disease for animals in Group 3 (controls) were similar to those described previously for this model [21-23]. Fever (Fig 2) was the earliest and most consistent finding, was measured for 6/8 animals in this group, was noted between Study Days 2-3, and peaked on Study Day 2.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Disease signs were typically noted between Study Days 2-9. Clinical signs of disease for animals in Group 3 (controls) were similar to those described previously for this model [21-23]. Fever (Fig 2) was the earliest and most consistent finding, was measured for 6/8 animals in this group, was noted between Study Days 2-3, and peaked on Study Day 2.…”
Section: Resultssupporting
confidence: 81%
“…Half of the animals in each group were randomly selected for euthanasia on Study Day 9, with the other half euthanized on Study Day 15. This euthanasia schedule was chosen to provide the best opportunity for assessing pathological findings, which are largely absent after Study Day 10, while still assuring that any delay in disease progression in vaccinated animals could be realized [21]. Clinical findings are summarized by study group in S1 Table . Disease signs were typically noted between Study Days 2-9.…”
Section: Vaccination With Spfn Reduces Clinical Disease In Sars-cov-2...mentioning
confidence: 99%
“…Exposure deeper in the trachea was found to induce lung lesion development earlier compared with exposure in the upper trachea (Table 1) [9,49,54,56,65]. Small-particle aerosol exposure is an alternative to direct inoculation [9,32,34,44]. Overall, viral load, clinical disease progression and severity, plasma cytokine concentrations, and pathology are similar in aerosol-exposed NHPs compared with those exposed via other routes [34].…”
Section: Open Accessmentioning
confidence: 97%
“…These sensitivity limitations also apply to imaging of SARS-CoV-2-exposed NHPs, and CXR has been widely used in research studies. Although most human CXR examinations are inconclusive during the early stages of COVID-19 [37], 28 studies of SARS-CoV-2-exposed NHPs detected CXR abnormalities early after exposure [9,[13][14][15][16][17][20][21][22][23]26,27,29,32,35,[44][45][46]. However, CXR imaging was inconclusive in other studies [12,13,[23][24][25]28] and was generally found to be uncorrelated with the degree of lung abnormalities at necropsy (Figure 1).…”
Section: Highlightsmentioning
confidence: 99%
“…It has also been shown in animal models that placing surgical masks around cages of infectious individuals reduced transmission ( 47 ). Animal models also show the aerosol exposure more likely leading to more severe disease and efficient transmission ( 48 , 49 ).…”
Section: Discussionmentioning
confidence: 99%